Towards a Methodology for Lipoprotein Ontology - Chen, Meifania; Hadzic, Maja (IEEE, 2010)
Abnormal plasma lipoprotein levels have been found to be significantly correlated to cardiovascular disease, the leading cause of mortality and morbidity worldwide. In addition, lipoprotein dysregulation, known as dyslipidemia, is a central feature in disease states such as diabetes and hypertension, which also increases the risk to cardiovascular disease. Despite progress in lipoprotein research, a vast number of the world population suffers from dyslipidemia. One of the major challenges that researchers face is the difficulties in accessing and integrating relevant information amidst massive quantities of heterogeneous data. Ontologies target these problems by providing a semantic framework of the concepts involved in a system of related instances to support systematic querying of information, data mining, as well as form the basis for collaboration between research teams. Lipoprotein Ontology will provide the basis for the design of various applications to enable interoperability between research groups or software agents, as well as the development of tools for the diagnosis and treatment of dyslipidemia. In this paper we present a nine-step methodology for the design of Lipoprotein Ontology. This methodology can be adapted for use in the design of other domain-specific ontologies.